5 - L’émergence et les perspectives de l’enseignement supérieur privé au Cameroun* - Ngwé, Luc (Journal of Higher Education in Africa, 2008)
Private higher education in Cameroon has developed considerably since its reform started in 1993. This development, which began when the state was relatively unprepared, has brought about a near exponential multiplication of institutions with different characteristics in terms of origin, nature, identity and status. These institutions also face different situations, especially in their structures, training programmes, variable action possibilities and differential positions in space. Beyond these differences, private higher education is still under the grip of the state which controls its dynamics through the accreditation system, structuring of training programmes, indirect sponsorship through the provision of personnel, etc. Finally, the sector remains rather fragile and calls for the questioning of its real development possibilities.